THE EFFECTS OF CUSTOMER VALUE AND SWITCHING BARRIER TO CUSTOMER LOYALTY AT PT. TELKOMSEL MANADO - Mintje, Saniati Muliani M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Customer value is customer’s perceived  preference for and evaluation of  those product or service. It is   one of factor that can attract customers. While, switching barrier is difficult of switch product or service by a customer who is not satisfied with the existing service. It is a factor that can keep customers. so, with definition of Customer Value and Switching barrier above, it can concluded that, by creating Customer value and Switching Barrier it can create customer loyalty. The Purpose of this research are to see the effects of customer value and switching barrier to customer loyalty. This research supporting by theories of about customer value, switching barrier and customer loyalty. The population of this research is customer of mobile operator Telkomsel in Manado, and use sample 100 respondents. Analyzed was a Multiple Regression analyze. The conclusion of this research are: customer value has no significant effect to customer loyalty; Switching barrier have effect to customer loyalty and, customer Value and Switching Barrier simultaneously Effects to Customer Loyalty.Keywords: customer value, switching barrier and customer loyalty.